TRANSFORMATIONAL OR INFORMATIONAL HOLIDAYS? AN ANALYSIS OF THE MESSAGE STRATEGIES FOR TECHNOLOGY BRANDS IN ROMANIA - ÎMPUȘCATU ROLAND (Styles of Communication)
In today’s digital landscape, social media platforms, particularly Facebook, play a pivotal role in shaping consumer-brand interactions, especially in high-interest sectors such as the smartphone market in Romania. This study investigates which message strategies are associated with higher levels of user engagement on the Facebook pages of two leading smartphone brands, Samsung and Xiaomi. The research explores the dynamics between messaging strategies (informational and transformational) and user engagement, providing insights into the digital advertising strategies adopted by these brands during the crucial holiday shopping season. The findings suggest that the informational dimension, notably ration message strategy, generated different types of engagement. In particular, ration led to higher levels of sharing than ego. Furthermore, regarding reactions, ration resulted in greater engagement than ego, routine and sensory. This research contributes to understanding digital consumer engagement and provides valuable insights for marketers seeking to optimize social media strategies in the competitive smartphone market.